The Impact of Instrumental Enrichment Strategy on Achievement in Mathematics for Second Intermediate Female Students (Journal of the College of Basic Education, 2019)
The present study impact of instrumental enrichment strategy on achievement in mathematics for second intermediate female students through testing one null hypothese :.there is no statistically significant difference between the mean scores of the experimental group students who were taught by using instrumental enrichment strategy and the control group students who were taught by using the traditional method in mathematics achievement test.The study sample was selected fromAl-Rhma Intermediate school for girls of Al-Russafa the third Directorate. The experiment was applied during the second semester of the academic year (2018-2019), After excluding the repeaters for consisted of (71) female students have been distributed into (34) students represents the experimental group and (37) students represents the control group. The equivalence of the study group in variables of age, intelligence, previous achievement in mathematics, previous knowledge test. And for measuring the two groups in their achievement in mathematics, the researcher has prepared an achievement test consisted of (20) multiple choice items. After ensuring the test validity, reliability, and difficulty level for the two tests items, it has been applied. The researcher has used several statistical tools for analyzing data such as (T. test), (X²) test and (SPSS).The obtained results are as follows:.1-there is a statistically significant difference between the mean scores of the experimental and control group in mathematic achievement test in favor of the experimental group. The researcher believes that the superiority of the experimental group to the control group is due to the impact of instrumental enrichment strategy. Complementing this study, the researcher has suggested study to investigate the obstacles of applying instrumental enrichment strategy in teaching mathematics at intermediate and preparatory school